2002
DOI: 10.1183/09031936.02.00270802
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in staging for lung cancer

Abstract: Computed tomography (CT) provides the most detailed imaging information, hence it is generally used as a routine imaging procedure in the tumour, node, metastasis (TNM)-staging of patients with lung cancer. However, despite the continuously ongoing process of improvement in CT scanning in which today9s CT scanners combine fast acquisition, fast data reconstruction and high detail, the technique has important limitations.CT can, in some cases, very accurately show tumour extent within, and predict spread beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 93 publications
(98 reference statements)
0
30
0
Order By: Relevance
“…CT provides precise characterization of the size, contour, extent and tissue composition of the suspicious lesion. 6 Staging lung cancer is, of course, a multidisciplinary process, which also utilizes other procedures such as bronchoscopy and biopsy. The diagnostic yield of bronchial biopsy specimens varies from 70 to 90 percent depending on the site and type of tumour.…”
mentioning
confidence: 99%
“…CT provides precise characterization of the size, contour, extent and tissue composition of the suspicious lesion. 6 Staging lung cancer is, of course, a multidisciplinary process, which also utilizes other procedures such as bronchoscopy and biopsy. The diagnostic yield of bronchial biopsy specimens varies from 70 to 90 percent depending on the site and type of tumour.…”
mentioning
confidence: 99%
“…In this study we acquired relatively high values for sensitivity, specificity, and accuracy with thin-section SS-TSE-HF images only, and the results were better than those with CT or conventional MRI (dynamic MRI, THRIVE, and conventional axial SS-TSE-HF) and were also comparable with the combination of static and dynamic MR images on prior studies (6,10,(21)(22)(23). We obtained relatively high sensitivity for detecting local invasion of lung cancer for CT, thin-section SS-TSE-HF, and conventional MRI.…”
Section: Discussionmentioning
confidence: 55%
“…Magnetic resonance imaging (MRI) can be superior to CT scanning in delineating direct tumor invasion of contact structures with higher tissue contrast (5) and previous reports have shown that the use of contrast enhancement might improve the accuracy of MRI for lung cancer invasion (6,7). Recently, several studies have reported that dynamic MRI such as electrocardiogram (ECG)-gated cardiac cine MRI or respiratory dynamic MRI can improve the prediction accuracy of adjacent mediastinal vascular structures or chest wall invasion of lung cancer (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…First, the cause of the lesion must be determined, and second, in the case of malignancy, it is crucial to determine the correct stage. The advanced computed tomography (CT) technique has had a major influence on the detection of suspected malignant lung nodules [1]. Both smaller and increasing numbers of nodules can now be detected because of improvement in scan resolution [2,3] and screening for lung cancer with CT is gaining ground.…”
Section: Introductionmentioning
confidence: 99%